Kulturkampf na obszarze ołomunieckiego komisariatu arcybiskupiego z siedzibą w Kietrzu (1871–1878) - Katarzyna Maler (Wrocławski Przegląd Teologiczny)
At present, Głubczyce area covers southern part of Opole Voivodship.It is bordered with the Chech Republic in the south and west. The territory was excluded from Poland for over 900 years, from 1038 to 1945. In the Church terms, up to 1945 the territory belonged to the Chech Olomouc diocese . After the First Prussian War in 1742 it was handed over from the power of the Austrian Habsburgs under control of Prussia. The newly established border separated Prussian Silesia from the Habsburg monarchy and divided Olomouc diocese into two parts. The bigger one, with the capital in Olomouc, stayed within the Habsburg monarchy. The smaller part, containing Głubczyce area, was assigned to the New Kingdom of Prussia. In this Prussian enclave of Olomouc bishopric, in 1751 Frederic II, the King of Prussia, initiated the foundation of Olomouc Bishop Commissioner with his registered office in Kietrz, Głubczyce County. The commissioner became the intermediary between Olomouc bishopric and the priesthood and believers of some deaneries in his area. He was also the intermediary between Olomouc bishopric and the governing bodies of Prussia. The Bishop Commissioner served in most of the territory of Głubczyce county and in some parts of Racibórz county.